The application of Islamic laws in cyber related cases: An analysis - Mohamed, Duryana; Hussin, Nasimah (2013)
Development in technology has created many opportunities for the Muslims to explore and acquire knowledge. Some Muslims are conscious when using the technology while some others are behaving inappropriately. The later groups are those who commit unlawful act which sometimes across the boundaries. These offences may cause harm not only to individuals but the country as a whole. Among the offences that have affected the society include internet fraud, internet pornography, unauthorised access to others computer data, internet defamation, cyber terrorism and many others. The Government of Malaysia has made several efforts to curb these activities from spreading. One of them is by introducing cyberlaws in addition to the existing laws of Penal Code, Defamation Act and other relevant statutes. However, statistics from the Cyber security and Royal Malaysian Police show that cyber offences are still increasing and causing threat not only to the society but also to the economic, political and security of the country. This is proven when the statistics of the Royal Malaysian Police recorded that the highest reported case in 2010 was crimes related to misuse of ATM and the highest loss amounting to RM20,786,906.62 was caused by syndicate activities on banking. Several court cases have also shown that those suspects are caught and charged under the above laws or known also as ‘man-made laws.’ Some of them are released and acquitted while some others are fined and jailed or both for certain period of time. An example can be seen from a case involving a blogger who posted defamatory statements on the internet against Datuk Seri Dr Rais Yatim , an Information, Communication and Culture Minister. The blogger was ordered by the High Court of Kuala Lumpur to pay RM300,000 to Dr Rais for the offence committed. This case shows that when a person has made wrongful statements against another person and the information was distributed over the internet to others, the victim may sue that person and claim for damages. The same also applies in Islamic law where a Muslim is prohibited from spreading rumors and back biting. However, there is no specific Shari‘ah provision on this matter. Thus, this paper will discuss the matter by looking at the types of cyber offences, how the Shari‘ah law categorised those offences, the position of those offences in the Shari‘ah statutes (if any) and relevant punishment to be imposed on the offender. Lastly, the challenges in implementing the Shari‘ah laws in cyber related cases in Malaysia will be highlighted and further analysed. (416 words)